1991
DOI: 10.1021/np50073a010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,3,4,8-Tetraoxygenated Xanthones

Abstract: Six 1,3,4,8-tetraoxygenated xanthones are synthesized. The possibility of a 1,3,4,8-tetraoxygenated pattern for two xanthones from Centaurium linarifolium is disproved. New structures are proposed for these two xanthones as 1,3,5-trihydroxy-2-methoxyxanthone, already cited in the literature, and 1,3-dihydroxy-2,5-dimethoxyxanthone, not previously cited.During the past 30 years, a large number of xanthones have been isolated from higher plants and their natural occurrence and synthesis have gained considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Table 2 presents natural products whose syntheses have been reported in the last twenty years by the reasons stated above. Nevertheless, in the 80s and 90s, several studies still reported syntheses of xanthones as a methodology to assign unambiguously the structures of isolated compounds [174][175][176]. For previous studies, considering the synthesis of phytoxanthones, see references [8,9].…”
Section: Synthesis Of Natural Productsmentioning
confidence: 99%
“…Table 2 presents natural products whose syntheses have been reported in the last twenty years by the reasons stated above. Nevertheless, in the 80s and 90s, several studies still reported syntheses of xanthones as a methodology to assign unambiguously the structures of isolated compounds [174][175][176]. For previous studies, considering the synthesis of phytoxanthones, see references [8,9].…”
Section: Synthesis Of Natural Productsmentioning
confidence: 99%
“…In a review of Hypericum genus, Kitanov and Blinova (1987) listed only ®ve simple tetraoxygenated xanthones; two years later, in a review of xanthones from 1-Hydroxy-2,3,7-trimethoxyxanthone (4) F. caroliniensis [313] Halenia elliptica [38,87] Veratrilla baillonii [348] 1-Hydroxy-3,4,5-trimethoxyxanthone (5) Frasera albicaulis [314] 1-Hydroxy-3,4,7-trimethoxyxanthone (6) Frasera albicaulis [314] F. albomarginata [90] 1-Hydroxy-3,5,6-trimethoxyxanthone (7) Canscora decussata [108] Centaurium erythraea [190] Hoppea dichotoma [110] (Haploxanthone) Calophyllum apetalum [165] Calophyllum bracteatum [312] C. inophyllum [171] C. tomentosum [28] C. trapezifolium [128] Centaurium linarifolium [114] Kayea stylosa [131] Monnina obtusifolia [283] Pentadesma butyracea [81] Tovomita pyrifolium [245] 1,3,5-Trihydroxy-6-methoxyxanthone (68)…”
Section: Tetraoxygenated Xanthonesmentioning
confidence: 99%